Utveckling av staket med integrerad solcellsteknik - El Masri, Mohammed Ali; Forsman, Niklas (My University, 2024)
This study aims to develop an embodied concept for a fence with integrated solar cell technology, specifically designed for gardens and urban environments. The project, commissioned by Raymond Solar AB, focuses on creating a scalable and sustainable product that meets both current and future demands within solar energy, while being tailored to the Nordic climate and compatible with Raymond Solar’s existing products. The central challenge is designing a fence that is cost-effective to manufacture and easy to assemble, while ensuring that it withstands the climatic challenges, has a low environmental impact, and is both functional and aesthetically pleasing. A particular challenge was to make the fence adjustable to allow for some tolerance in the positioning and inclination of the ground screws, which is crucial for ensuring a smooth and rapid installation. Additionally, the construction needed to be compatible with different types and sizes of solar panels to maximize flexibility. The project was conducted through a combination of literature reviews, competitor analyses, and computer-assisted testing. Traditional technologies and competitor solutions were thoroughly examined to gather relevant data. Functional analyses and specifications were established to ensure that the product meets all necessary functions and requirements. CAD software was used for design, while strength analyses were conducted using FEA software. The study resulted in a modular fence construction made of aluminum, with posts, bottom rails, panels, footings, and fittings. The design is easy to assemble with few screws and includes T-slots for flexible installation of solar panels. Additionally, the fence is ergonomic and time-saving during installation, and the design allows for adjustments to handle deviations in the placement and inclination of ground screws. The construction is also compatible with various types and dimensions of solar panels, increasing flexibility and enabling adaptation to different installation needs. The production offers the possibility of using recycled materials, and the fence is fully recyclable, significantly reducing its environmental impact. The study concludes that the developed fence with integrated solar cell technology meets the criteria for sustainability, cost-effectiveness, and ease of assembly. The robust construction ensures that the fence can withstand the challenges of the Nordic climate and offers a solution that is both environmentally friendly and practical for consumers and installers